Environmental discourses in public and international law - Jessup, Brad 1978-; Rubenstein, Kim (Connecting international law with public law, 2012)
"This collection of essays examines the development and application of environmental laws and the relationship between public laws and international law. Notions of good governance, transparency and fairness in decision-making are analysed within the area of the law perceived as having the greatest potential to address today's global environmental concerns. International trends, such as free trade and environmental markets, are also observed to be infiltrating national laws. Together, the essays illustrate the idea that in the context of environmental problems being dynamic and environmental changes appearing suddenly, laws become difficult to design and effect. Typically, they are also devised within a conflicted setting. It is in this changeable and discordant context that environmental discourses such as precaution, justice, risk, equity, security, citizenship and markets contribute to legal responses, present legal opportunities or hinder progress"-- Provided by publisher.